Ultraviolet-resistant nylon composite material as well as preparation method and application thereof
Through the melt blending and extrusion technology of modified bismuth compounds and nylon elastomers, the problem of aging under ultraviolet light after the nylon elastomers and bismuth compounds is solved, and the UV aging resistance and mechanical properties of the catheter are improved.
Patent Information
- Application Number
- CN202411916740.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-02-07
AI Technical Summary
After the nylon elastomer is combined with bismuth compound, the nylon elastomer will age rapidly during ultraviolet curing hydrophilic coating treatment, resulting in discoloration and mechanical properties degradation. The interface interaction force between the bismuth compound powder and nylon elastomer is weak. This leads to a large number of crystal points on the surface of the catheter and a high product scrap rate.
Modified bismuth compounds are prepared by reacting the bismuth compound with a specific modifier such as 2-hydroxy-4-(3-triethoxysilanepropoxy)benzone. , and melt blended with nylon elastomer to form a nylon composite material that is resistant to ultraviolet.
The modified bismuth compound has better dispersibility in the nylon matrix, and has significantly improved UV aging resistance and mechanical properties. The color of the catheter does not change after ultraviolet light, the surface does not crack, and the tensile strength remains stable.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of interventional medical technology, in particular to a UV-resistant nylon polymer composite material, a preparation method thereof and application thereof in the field of interventional medical technology. Background Art
[0002] In recent years, interventional therapy has developed rapidly and is the third fastest growing therapeutic discipline after internal medicine and surgery. It makes up for the shortcomings of internal and surgical techniques. Interventional therapy technology has the characteristics of less trauma, more indications, definite efficacy, and fast postoperative recovery. It is an important development trend of future medicine. In interventional therapy technology, one of the indispensable medical devices is the interventional catheter. The interventional catheter is usually a multi-layer composite pipeline, in which the outermost layer of the catheter is a developing composite material pipeline, which is composed of polymer materials and developers. Among many polymer materials, nylon elastomers are the most commonly used because of their high resilience and torque conductivity. The developer mainly uses barium sulfate, bismuth compounds and tungsten compounds, among which bismuth compounds have the best development effect, so the composite nylon and bismuth compound catheters are more and more widely used. In addition, in order to reduce the push assist of the interventional catheter, a UV-cured hydrophilic coating is usually introduced on the surface of the interventional catheter.
[0003] However, bismuth compounds have ultraviolet light catalytic activity. When nylon elastomers are composited with bismuth compounds to prepare catheters, and a UV-cured hydrophilic coating is applied to their surfaces, the nylon elastomers will age rapidly, discolor, and suffer from mechanical property degradation. In addition, bismuth compound powders also have the problem of weak interfacial interaction with nylon elastomers, resulting in a large number of crystal points on the surface of catheters prepared from the composites, and a high product scrap rate. These problems limit the application of bismuth-developable nylon composite materials with excellent development effects in interventional catheters. Therefore, the development of a UV-resistant nylon elastomer composite material has important application value. Summary of the invention
[0004] In view of this, an object of the present invention is to provide a UV-resistant nylon composite material and a preparation method and application thereof.
[0005] The present invention is implemented by the following technical solutions: A UV-resistant nylon composite material, characterized in that it consists of the following components: a) Nylon elastomer, 40 to 90 parts by weight; b) a modified bismuth compound, in an amount of 10 to 60 parts by weight; The modified bismuth compound is prepared by: The bismuth compound and anhydrous ethanol are mixed in a mass ratio of 1:0.1 to 1:10, ammonia water is added until the pH value of the solution is 8 to 10, the solution is heated to 60 to 75° C., a modifier having a mass fraction of 0.2% to 2% of the bismuth compound is added, the solution is reacted for 4 to 8 hours, and then centrifuged and dried to obtain a modified bismuth compound; The modifier is selected from one or more of 2-hydroxy-4-(3-trimethoxysilanepropoxy)benzophenone, 2-hydroxy-4-(3-triethoxysilanepropoxy)benzophenone, 2-hydroxy-4-(3-tripropoxysilanepropoxy)benzophenone, and 2-hydroxy-4-(3-tributoxysilanepropoxy)benzophenone, preferably 2-hydroxy-4-(3-triethoxysilanepropoxy)benzophenone; and the nylon composite material has an X-ray development function.
[0006] The nylon is selected from one or more of nylon 12, nylon 6, nylon 66, nylon 11, nylon 46, nylon 610, nylon 612, nylon 1010, nylon 1212 and polyether modified nylon elastomer, preferably polyether modified nylon elastomer, and the number average molecular weight of the nylon is 8000-30000.
[0007] The bismuth compound is selected from one or more of bismuth basic carbonate, bismuth oxychloride or bismuth trioxide, preferably bismuth basic carbonate, and the average particle size D50 of the bismuth compound (measured by laser diffraction scattering method) is 0.05-10 μm, preferably 0.5-8 μm, more preferably 1-6 μm, and most preferably 2 μm. When the particle size of the bismuth compound is too small, the cost will increase significantly; and when the particle size of the bismuth compound is too large, the surface roughness of the catheter will increase. Exemplarily, the amount of nylon can be 40 parts, 45 parts, 50 parts, 55 parts, 60 parts, 65 parts, 70 parts, 75 parts, 80 parts, 85 parts, 90 parts, preferably, the amount of nylon is 55-85 parts, and 80 parts is most preferred; the amount of the modified bismuth compound can be 60 parts, 55 parts, 50 parts, 45 parts, 35 parts, 30 parts, 25 parts, 20 parts, 25 parts, 20 parts, 15 parts, 10 parts, preferably, the amount of the modified bismuth compound is 15-45 parts, and 20 parts is most preferred.
[0008] In the above technical scheme, a drying method familiar to those skilled in the art is adopted, including but not limited to drying or vacuum drying. The present invention preferably adopts a vacuum drying method, and the vacuum drying temperature is preferably 50-80°C, more preferably 60°C, and the drying time is 2-12h.
[0009] The present invention also provides a method for preparing a UV-resistant nylon composite material, comprising the following steps: adding a modified bismuth compound and a nylon resin into a loss-in-weight feeder respectively, and then independently and continuously adding them into a twin-screw extruder for melt mixing and dispersion, and processing and forming to obtain a UV-resistant nylon composite material.
[0010] The rotation speed of the twin-screw extruder is preferably 100-300 rpm; the residence time is preferably 2-3 min, the temperature setting of each working section of the twin-screw extruder is preferably 200±20°C, 210±20°C, 220±20°C, 230±20°C, 230±20°C, and the die head temperature is preferably 200±20°C. After extrusion, water cooling and granulation are performed to obtain a UV-resistant nylon composite material with X-ray development function.
[0011] The present invention claims protection for a biomedical material, characterized in that it comprises the UV-resistant nylon composite material.
[0012] The present invention claims protection for an interventional catheter, characterized in that it comprises the UV-resistant nylon composite material.
[0013] When used in other fields, the UV-resistant nylon composite material of the present invention may optionally contain plasticizers, fillers, pigments, desiccants, catalysts, binders and / or other auxiliary substances and additives.
[0014] Compared with the prior art, the present invention has the following advantages: 1) a modified bismuth compound and a preparation method thereof are invented, wherein a modified bismuth compound is obtained by selecting a specific modifier to react with the bismuth compound; the modifier can not only play the role of ultraviolet light absorption, but also play the role of a coupling agent, thereby realizing surface modification of the bismuth compound and improving the dispersibility of the bismuth compound in the nylon matrix; the modifier and the bismuth compound are combined together by covalent chemical bonds, and are more resistant to precipitation; 2) The nylon composite material containing the modified bismuth compound has good UV aging resistance and improved mechanical properties while maintaining good X-ray imaging function; 3) The UV-resistant composite material can be used for the preparation of catheters. When the prepared catheter is treated with UV-cured hydrophilic coating, the color of the catheter does not change, and the surface does not crack after accelerated aging at 60°C for 90 days. 4) The UV-resistant nylon composite material is prepared by a twin-screw extruder melt blending extrusion method. The preparation method is simple, low-cost, and can be used in large-scale industrial production. DETAILED DESCRIPTION
[0015] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in the present invention.
[0016] Synthesis example 1: Bismuth basic carbonate with an average particle size D50 of 2 μm and anhydrous ethanol are mixed in a mass ratio of 1:0.5, ammonia water is added until the solution pH is 9, the solution is heated to 65° C., and a 2-hydroxy-4-(3-triethoxysilanepropoxy)dibenzophenone modifier with a mass fraction of 1% of the bismuth compound is added. After reacting for 6 hours, the solution is centrifuged and vacuum dried at 60° C. for 6 hours to obtain a modified bismuth compound.
[0017] Synthesis example 2: Bismuth trioxide with an average particle size D50 of 2 μm and anhydrous ethanol are mixed in a mass ratio of 1:1, ammonia water is added until the solution pH is 10, heated to 65°C, and a 2-hydroxy-4-(3-triethoxysilanepropoxy)dibenzophenone modifier with a mass fraction of 1% of the bismuth compound is added. After reacting for 6 hours, centrifugation and vacuum drying at 65°C for 5 hours are performed to obtain a modified bismuth compound.
[0018] Synthesis example 3: Bismuth oxychloride with an average particle size D50 of 2 μm and anhydrous ethanol are mixed in a mass ratio of 1:3, ammonia water is added until the solution pH is 9, the solution is heated to 60°C, and a 2-hydroxy-4-(3-triethoxysilanepropoxy)dibenzophenone modifier with a mass fraction of 1% of the bismuth compound is added. After reacting for 6 hours, the solution is centrifuged and vacuum dried at 70°C for 5 hours to obtain a modified bismuth compound.
[0019] Synthesis example 4: Bismuth basic carbonate with an average particle size D50 of 2 μm and anhydrous ethanol are mixed in a mass ratio of 1:1, ammonia water is added until the solution pH is 9, the solution is heated to 65° C., a 2-hydroxy-dibenzophenone modifier with a bismuth compound fraction of 1% is added, the reaction is carried out for 6 hours, the solution is centrifuged, and vacuum dried at 60° C. for 6 hours to obtain a modified bismuth compound.
[0020] Example 1 A UV-resistant nylon composite material is composed of the following raw materials in parts by weight: Nylon elastomer Pebax 7233, 80 parts by weight; The modified bismuth compound of Synthesis Example 1, 20 parts by weight.
[0021] The above-mentioned UV-resistant nylon composite material is prepared by the following steps: weighing materials according to mass fractions, and pre-vacuum drying the weighed Pebax 7233 at 85°C for 4 hours; respectively putting the dried nylon resin and the modified bismuth compound of Synthesis Example 1 into a clean loss-in-weight feeder, setting the nylon elastomer feeding speed to 8.0kg / h and the bismuth compound to 2.0kg / h, and continuously adding them into a twin-screw extruder, setting the temperature to 200-230°C, and melt-extruding the mixture, cooling, pelletizing, homogenizing, drying, and sealing to obtain the UV-resistant nylon composite material.
[0022] Example 2-3 The preparation method is the same as that of Example 1, except that the modified bismuth compound of Synthesis Example 1 is replaced by those of Synthesis Examples 2-3 respectively.
[0023] Comparative Example 1 The preparation method is the same as that of Example 1, except that the modified bismuth compound of Synthesis Example 1 is replaced by unmodified bismuth basic carbonate.
[0024] Comparative Example 2 The preparation method is the same as that of Example 1, except that the modified bismuth compound of Synthesis Example 1 is replaced by 20 parts of pure basic bismuth carbonate, and at the same time, 0.2 parts of 2-hydroxy-4-(3-triethoxysilanepropoxy)dibenzophenone is added during the twin-screw extrusion process.
[0025] Comparative Example 3 The preparation method is the same as that of Comparative Example 2, except that the bismuth basic carbonate in Comparative Example 2 is replaced by bismuth trioxide.
[0026] Comparative Example 4 The preparation method is the same as that of Example 1, except that the modified bismuth compound of Synthesis Example 1 is replaced by that of Synthesis Example 4.
[0027] Comparative Example 5 The preparation method is the same as that of Comparative Example 2, except that the 2-hydroxy-4-(3-triethoxysilanepropoxy)benzophenone in Comparative Example 2 is replaced by Antioxidant 1098.
[0028] In order to simulate the actual application of the catheter, the nylon composite materials prepared in Examples 1-3 and Comparative Examples 1-5 were vacuum dried at 85°C for 4 hours, cast into a film with a thickness of 0.1 mm (this thickness is consistent with the thickness of most catheters), the casting temperature was 200-230°C, the cooling roller temperature was 20°C, and then tested according to the standard. The performance test results are shown in Table 1: performance Test Standards Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Tensile strength(MPa) GB / T 528 47 46 46 41 43 44 42 42 <![CDATA[Number of surface crystal points (pcs / 10 cm 2 )]]> Visual none none none 6 4 8 6 6 UV absorbance (220nm) GB / T14233.1 0.04 0.05 0.04 0.04 0.22 0.19 Greater than detection limit 0.06 <![CDATA[Color change (under 365 nm UV light of 100 mW / cm 2 for 3 min)]]> Visual White Yellowish white Pearlescent white Obvious yellowing Slight yellowing Slight yellowing Slight yellowing Obvious yellowing Appearance after 3 months of heat aging at 60℃ after UV irradiation Visual The surface is smooth and complete, slightly yellow The surface is smooth and complete, slightly yellow The surface is smooth and complete, slightly yellow There are obvious cracks on the surface, light yellow There are slight cracks on the surface, light yellow The surface has slight cracks and gray spots There are slight cracks on the surface, light yellow There are obvious cracks on the surface, and it is obviously yellow Tensile strength after heat aging at 60℃ for 3 months after UV irradiation (MPa) GB / T 528 44 40 42 Unable to test 26 22 25 Unable to test Examples 1-3 use surface-modified bismuth compounds to prepare nylon elastomer composite materials, and the ultraviolet absorber forms a surface-coated ultraviolet barrier layer on the surface of the bismuth compound. Compared with the method of using pure bismuth compounds in Comparative Example 1, the ultraviolet response of the bismuth compound is avoided, and the interaction between the bismuth compound and the nylon elastomer is enhanced, resulting in better dispersibility.
[0029] In the modified bismuth compounds of Examples 1-3, the modifier and the bismuth compound undergo a chemical reaction to form a whole. In addition, the pre-surface treatment process also cleans away impurities in the modifier. Compared with Comparative Examples 2 and 3, which only shield ultraviolet radiation by physical blending, the number of crystal points is significantly reduced, the mechanical strength is higher, and the ultraviolet radiation resistance is increased. In addition, the ultraviolet absorbance of Examples 1-3 is lower (referring to the GB / T14233 test, the ultraviolet absorbance represents the amount of precipitate content. As a medical device application, many medical devices limit the absorbance value to within 0.08).
[0030] Compared with Comparative Example 4, in Examples 1-3, the bismuth compound and the modifier in Comparative Example 4 were only physically mixed, the modifier was easily precipitated, and its ultraviolet absorbance exceeded the instrument detection limit, which could not meet the requirements of medical applications.
[0031] Compared with Example 5, Example 5 uses a nylon-specific antioxidant, and its ultraviolet aging performance, dispersion uniformity and anti-precipitation performance are all inferior to those of Example 1, which further illustrates the positive effect of the ultraviolet absorber.
[0032] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A UV-resistant nylon composite material, characterized in that: It is composed of the following components: a) Nylon elastomer, 40 to 90 parts by weight; b) a modified bismuth compound, in an amount of 10 to 60 parts by weight; The modified bismuth compound preparation method comprises: mixing a bismuth compound and anhydrous ethanol at a mass ratio of 1:0.1 to 1:10, adding ammonia water until the solution has a pH value of 8 to 10, heating to 60 to 75° C., adding a modifier having a mass fraction of 0.2% to 2% of the bismuth compound, reacting for 4 to 8 hours, centrifuging, and drying to obtain the modified bismuth compound; the modifier is selected from one or more of 2-hydroxy-4-(3-trimethoxysilylpropoxy)benzophenone, 2-hydroxy-4-(3-triethoxysilylpropoxy)benzophenone, 2-hydroxy-4-(3-tripropoxysilylpropoxy)benzophenone, and 2-hydroxy-4-(3-tributoxysilylpropoxy)benzophenone; The nylon composite material has an X-ray development function.
2. The UV-resistant nylon composite material according to claim 1, characterized in that: The nylon is selected from one or more of nylon 12, nylon 6, nylon 66, nylon 11, nylon 46, nylon 610, nylon 612, nylon 1010, nylon 1212 and polyether modified nylon elastomer.
3. The UV-resistant nylon composite material according to claim 1, characterized in that: The modifier is 2-hydroxy-4-(3-triethoxysilane propoxy) benzophenone, and the nylon is a polyether-modified nylon elastomer.
4. The UV-resistant nylon composite material according to claim 1, characterized in that: The bismuth compound is selected from one or more of bismuth basic carbonate, bismuth oxychloride or bismuth trioxide, and the average particle size D50 of the bismuth compound is 0.05-10 μm.
5. The UV-resistant nylon composite material according to claim 1, characterized in that: The nylon is Pebax7233, and the amount used is 80 parts; the modified bismuth compound is bismuth basic carbonate with an average particle size of 2 μm modified by 2-hydroxy-4-(3-triethoxysilanepropoxy)dibenzophenone, and the amount used is 20 parts.
6. A method for preparing a UV-resistant nylon composite material as described in claim 1, comprising the following steps: adding the modified bismuth compound and the nylon resin to a loss-in-weight feeder respectively, and then independently and continuously adding them to a twin-screw extruder for melt mixing and dispersion, and processing and forming to obtain a UV-resistant nylon composite material.
7. A biomedical material, characterized in that: The invention comprises the UV-resistant nylon composite material as claimed in claim 1.
8. An interventional catheter, characterized in that: The invention comprises the UV-resistant nylon composite material as claimed in claim 1.
Citation Information
Patent Citations
Tubular material with X ray developing function, and preparation method thereof
CN108276638A
Lubricating oil additive and preparation method thereof
CN112522000A
Polymer waterproof material and preparation method thereof
CN112646247A
Laser-marked anti-aging nylon glass fiber-reinforced flame-retardant composite material
CN114058176A
Nylon 12 composite material, preparation method thereof, medical intervention pipe and medical instrument
CN115716987A